Periodic solutions of neutral functional differential equations - Afonso, S. M. [UNESP] (2023)
We provide sufficient conditions for the existence and uniqueness of periodic solutions of a general class of neutral functional differential equations of type [Formula presented] defined almost everywhere in R. As a consequence, we study the existence and uniqueness of periodic solutions for this class of NFDEs under impulse perturbations. Examples are presented to illustrate the developed theory.